2012
DOI: 10.1016/j.acthis.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal accumulation of human transmembrane (TMEM)-176A and 176B proteins is associated with cancer pathology

Abstract: Transmembrane (TMEM)-176A and 176B proteins belong to the MS4A family of proteins whose function in the immune system remains unclear. TMEM176A transcripts were previously shown to be elevated in liver cancer or kidney tissue with proteinuria, while marked changes in TMEM176B transcripts have been found in tolerated tissue allografts and neoplastic fibroblasts. To study the functional relationship between human TMEM176A and 176B and their putative link to cancer, we used polymerase chain reaction and biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 18 publications
1
72
0
Order By: Relevance
“…18,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Several identified SNPs were located in or near genes that might be involved in biological pathway leading to lung function impairment (ie, GALNT13 and PCDH9, respectively). GALNT13 belongs to the GalNAcT family of enzymes, which initiate O-glycosylation of mucins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Several identified SNPs were located in or near genes that might be involved in biological pathway leading to lung function impairment (ie, GALNT13 and PCDH9, respectively). GALNT13 belongs to the GalNAcT family of enzymes, which initiate O-glycosylation of mucins.…”
Section: Discussionmentioning
confidence: 99%
“…31 Another study showed that TMEM16A expression levels in the lungs were low, yet proteins levels were increased in patients with lung carcinoma. 43 CHR, Chromosome; FVC, forced vital capacity.…”
Section: Discussionmentioning
confidence: 99%
“…1, Panel B). It is notable that the accumulation of TMEM176A/B has been linked to several other cancer types 21 previously. Moreover, we also found non-membrane associated genes with exclusive intron expression that are known to have links to cancer, such as secretagogin (SCGN) 22 involved in cell proliferation, the cytochrome P450 epoxygenase CYP2J2 23 or the hypoxia-inducible factor EGLN3.…”
Section: Resultsmentioning
confidence: 81%
“…Other top-ranked membrane-associated proteins show stronger known links to cancer, such as the transmembrane collagen COL23A1 20 or the transmembrane protein 176A. 21 Encouragingly, the latter as well as its heterologous protein TMEM176B also appeared on top of the list of genes that show exclusive intron expression and harbor significant sQTL (Fig. 1, Panel B).…”
Section: Resultsmentioning
confidence: 99%
“…Real-time qPCR was performed as previously described (Cuajungco et al, 2012), with minor modifications appropriate for our experiments. The amplification reactions were performed in a Bio-Rad CFX96 machine using SensiMix SYBR Green Master Mix (Bioline) with the following thermocycling conditions: 5 min at 95 uC followed by 40 cycles of 30 s at 95 uC, 45 s at 55 uC, 30 s at 72 uC.…”
Section: [For Cultures Lacking Both Fabh and (P)ppgpp] And 1610mentioning
confidence: 99%